The Effect of Investments and Risk Based Capital (RBC) of Tabarru Funds on Company (Case Study of Sharia Insurance in Indonesia for 2014-2019) - Nana Diana; Tati Apriani (International Journal of Nusantara Islam, 2020)
This study aims to examine the influence of investment returns and Risk Based Capital (RBC) Tabarru Funds to the profit of sharia life insurance in Indonesia from 2014-2019. This study The type of this research is quantitative research with descriptive verification as a method. This research method uses descriptive verification method with quantitative approach. The data used in this study were sourced from the financial statements of Islamic life insurance companies in Indonesia for the 2014-2019 period. Then the data obtained were analyzed using multiple linear regression analysis and hypothesis testing consisting of t test and f test with the help of SPSS 21 software. The sampling technique uses non probability sampling with purposive sampling technique. Based on the results of the study it can be seen that the development of investment returns on Sharia Life Insurance in Indonesia has fluctuated and even suffered losses. While the development of Risk Based Capital (RBC) has increased and decreased but overall above 120% as determined by the government. Likewise, the profits earned in each year fluctuate. The results of statistical tests show that investment results partially have a positive effect on profit and Risk Based Capital (RBC) of Tabarru funds partially has a negative effect on profit. Simultaneously investment return and Risk Based Capital (RBC) affect on profit. In addition, the results of the coefficient of determination (R2) were obtained which obtained a value of 81%. This shows that the variable investment returns and Risk Based Capital (RBC) can affect earnings by 81% and the remaining 19% is influenced by other variables not used in this study.